2020
DOI: 10.1371/journal.pone.0242090
|View full text |Cite
|
Sign up to set email alerts
|

The association of primary aldosteronism with glaucoma-related fundus abnormalities

Abstract: Purpose To elucidate glaucoma-related fundus abnormalities in patients with primary aldosteronism (PA). Methods The study compared 272 eyes from 137 PA patients and 352 eyes from 177 control subjects selected randomly from 1173 participants of a public glaucoma screening. The presence of glaucomatous optic disc appearance (rim thinning and cup enlargement) and retinal nerve fiber layer defects (RNFLDs) was determined independently from fundus photographs. The results were compared between the PA and control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…administered Aldo (40, 80, or 160 μg/kg/day) to rats and found that the RGC number was significantly reduced ( 49 ). Different from the animal experiment, compared with the control group, the patients with aldosteronism have no significant difference in their prognosis of glaucomatous optic disc appearance ( 11 ). Our MR results also found no causal relationship between aldosterone and glaucoma.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…administered Aldo (40, 80, or 160 μg/kg/day) to rats and found that the RGC number was significantly reduced ( 49 ). Different from the animal experiment, compared with the control group, the patients with aldosteronism have no significant difference in their prognosis of glaucomatous optic disc appearance ( 11 ). Our MR results also found no causal relationship between aldosterone and glaucoma.…”
Section: Discussionmentioning
confidence: 92%
“…After systemic administration of Aldo, Nitta et al (10) found progressive loss of retinal ganglion cells (RGCs) without elevated intraocular pressure (IOP), which means that PA will increase the glaucoma risk. Ohshima et al compared 137 glaucoma patients with PA and 177 controls and found no difference in the prevalence of glaucoma optic disc appearance between the two groups (11). Hao et al found that E2 can protect RGCs under a high glucose environment through the mitochondrial pathway (12).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Preclinical evidence showed that ischaemic ganglion cell death is enhanced by mineralocorticoid receptor pathway activation, that aldosterone causes ganglion cell loss and that spironolactone prevents excitotoxic ganglion cell death. In addition, a recent study showed that retinal nerve fibre layer defects were more frequent in patients with primary aldosteronism than in controls (Ohshima et al, 2020).…”
Section: Potential Of Mineralocorticoid Receptor Antagonis In Retinal...mentioning
confidence: 99%